Bài 2:
a: \(A=\dfrac{6}{23}+\left(\dfrac{5}{9}+\dfrac{-6}{23}\right)\)
\(=\dfrac{6}{23}+\dfrac{5}{9}-\dfrac{6}{23}\)
\(=\dfrac{5}{9}\)
b: \(B=-\dfrac{13}{27}+\left(-\dfrac{14}{7}+\dfrac{1}{7}\right)\)
\(=\dfrac{-13}{27}+\dfrac{-13}{7}\)
\(=\dfrac{-13\left(7+27\right)}{189}=\dfrac{-442}{189}\)
c; \(C=\left(-\dfrac{2}{9}+\dfrac{14}{33}\right)+\dfrac{19}{33}\)
\(=\left(-\dfrac{2}{9}\right)+\left(\dfrac{14}{33}+\dfrac{19}{33}\right)\)
\(=\dfrac{-2}{9}+1=\dfrac{7}{9}\)
Bài 1:
a: \(\dfrac{6}{13}+\dfrac{-14}{39}\)
\(=\dfrac{18}{39}-\dfrac{14}{39}\)
\(=\dfrac{4}{39}\)
b: \(\dfrac{-3}{21}+\dfrac{6}{42}\)
\(=\dfrac{-3}{21}+\dfrac{3}{21}\)
=0
c: \(\dfrac{-18}{24}+\dfrac{15}{21}\)
\(=\dfrac{-3}{4}+\dfrac{5}{7}\)
\(=\dfrac{-21+20}{28}=\dfrac{-1}{28}\)
d: \(\dfrac{1}{6}+\dfrac{2}{5}\)
\(=\dfrac{5}{30}+\dfrac{12}{30}\)
\(=\dfrac{17}{30}\)
e: \(\dfrac{3}{5}+\dfrac{-7}{4}\)
\(=\dfrac{12}{20}-\dfrac{35}{20}\)
\(=-\dfrac{23}{20}\)
f: \(-\dfrac{12}{18}+\dfrac{-21}{35}\)
\(=\dfrac{-2}{3}+\dfrac{-3}{5}\)
\(=\dfrac{-10+\left(-9\right)}{15}=\dfrac{-19}{15}\)
g: \(\dfrac{7}{21}+\dfrac{9}{-36}\)
\(=\dfrac{1}{3}-\dfrac{1}{4}\)
\(=\dfrac{4}{12}-\dfrac{3}{12}=\dfrac{1}{12}\)
h: \(\dfrac{1}{-8}+\dfrac{-5}{9}\)
\(=\dfrac{-9+\left(-5\right)\cdot8}{72}\)
\(=-\dfrac{49}{72}\)
i,4/13+ -( -12)/39
\(=\dfrac{4}{13}+\dfrac{12}{39}\)
\(=\dfrac{4}{13}+\dfrac{4}{13}=\dfrac{8}{13}\)
k,-(-1)/21 + 1/28
\(=\dfrac{1}{21}+\dfrac{1}{28}\)
\(=\dfrac{4+3}{84}=\dfrac{7}{84}=\dfrac{1}{12}\)
l, -5/9--5/12
\(=\dfrac{-5}{9}+\dfrac{5}{12}\)
\(=\dfrac{-5\cdot4+5\cdot3}{36}=\dfrac{-5}{36}\)